Predictive value of longitudinal whole-body magnetic resonance imaging in patients with smoldering multiple myeloma - Merz, Maximilian; Hielscher, Thomas; Wagner-Gund, Barbara; Sauer, Sandra; Shah, Sofia; Raab, Marc-Steffen; Jauch, Anna; Neben, Kai; Hose, Dirk; Egerer, Gerlinde; Weber, Marc-André; Delorme, Stefan; et al. (Leukemia, 2014)
Previous studies demonstrated the relevance of focal lesions (FL) in whole-body magnetic resonance imaging (wb-MRI) at the initial workup of patients with smoldering multiple myeloma (SMM). The aim of this study was to assess the effects of longitudinal wb-MRIs on progression into multiple myeloma (MM). Sixty-three patients with SMM were analyzed who received at least two wb-MRIs for follow-up before progression into MM. Radiological progressive disease (MRI-PD) was defined as detection of new FL or increase in diameter of existing FL and a novel or progressive diffuse infiltration. Radiological stable disease (MRI-SD) was defined by no change compared with the prior MRI. Patients were followed-up every 3-6 months, including a serological and clinical evaluation. One Hundred and eighty-two wb-MRIs were analyzed. MRI-PD occurred in 31 patients (49%), and 25 (40%) patients developed MM. MRI-PD was highly significantly associated with progression into MM, regardless of findings at the initial MRI. In multivariate analysis, MRI-PD remained a risk factor, independent of relevant baseline parameters like serum monoclonal protein or ⩾95% aberrant plasma cells in the bone marrow. Patients with MRI-SD had no higher risk of progression, even when FL were present at the initial MRI. Therefore, MRI is suitable for the follow-up of patients with SMM.